Directing for community theatre - Patterson, Daniel L. (Routledge, 2023)
Directing for Community Theatre is a primer for the amateur director working in community theatre. With an emphasis on preparedness, this book gives the amateur director the tools and techniques needed to effectively work on a community theatre production. Covering play analysis, blocking, staging, communication, and working with actors, designers, and other theatre personnel, this how-to book is designed to have the community theatre director up and running quickly, with full knowledge of how to direct a show. The book also contains sample forms and guidelines, including acting analysis, character analysis, rehearsal schedule, audition form, prop list, and blocking pans. Directing for Community Theatre is written for the community theatre participant who is interested, or already cast, in the role of the director"-- Provided by publisher.